Expression of a Novel Chimeric Truncated t-PA in CHO Cells Based on in Silico Experiments. (22nd September 2010) - Davami, Fatemeh; Sardari, Soroush; Majidzadeh-A, Keivan; Hemayatkar, Mehdi; Barkhrdari, Farzaneh; Omidi, Maryam; Azami, Mehrnaz; Adeli, Ahmad; Davoudi, Noushin; Mahboudi, Fereidoun
Abstract : Tissue plasminogen activator (t-PA) is one of the fibrin-specific serine proteases that play a crucial role in the fibrinolytic system. The rapid clearance of the drug from the circulation, caused by its active uptake in the liver, has lead to complicated clinical applications. Different forms of plasminogen activators have been developed to treat thrombotic disease. Deletion of the first three domains of t-PA by gene manipulation techniques has shown a significant increase in its plasma half life. In order to compensate the disadvantage of higher bleeding risk, a novel chimeric truncated form of t-PA with 394 amino acids and more fibrin affinity compared to the truncated form was designed to be expressed in Chinese Hamster Ovarian (CHO) cells. The recombinant chimeric plasminogen activator consists of kringle 2 and serine protease (K2S) domains of t-PA, namely GHRP-SYQ-K2S. The level of expression was found to be 752 IU/ml with 566, 917 IU/mg specific activity, based on amidolytic activity. The fibrin binding of this novel chimeric truncated t-PA was 86% of the full length t-PA at a fibrinogen concentration of 0.2 mg/ml. This could be a promising approach with more desirable pharmacodynamic properties compared to existing commercial forms.